Controle de potência reativa para adequação de valores de tensão e redução de perdas em redes elétricas com geração distribuída fotovoltaica - Lopes Filho, Gilberto (2024)
This work presents contributions aimed at improving the electrical voltage profile in compliance with regulatory standards and reducing or minimizing losses in a radial electrical network with distributed photovoltaic generation. By injecting reactive power in a controlled manner through inverters connecting their respective photovoltaic generators to the distribution network buses, it is possible to control network voltages and losses. This work proposes three distinct approaches. The first algorithm, based on observations of the electrical network’s behavior, determines generated reactive power values capable of reducing electrical losses and regulating voltage for various levels of distributed generation penetration and load power factor. The allocation of photovoltaic generators and power values is randomly generated, and through a Monte Carlo simulation, the performance of the proposal can be analyzed. The second proposal uses heuristic algorithms (Genetic Algorithm and Firefly Algorithm) to estimate optimal reactive power values at the buses, aiming at voltage regulation, minimization of electrical losses, or minimization of losses with constraints on voltage magnitude values. The third proposal employs analytical relationships between reactive power, power loss, and voltage deviation to control reactive power injections into the electrical network. These analytical relationships, derived from the equations in this work, ensure computational simplicity while optimizing loss reduction and voltage deviation. This proposal includes the Loss Reduction Algorithm (LRA) and the Voltage Regulation Algorithm (VRA) and introduces an approach to efficiently switch between them called the Combined Control Strategy (CCS). The CCS seeks to provide a balance between voltage regulation and the reduction of electrical losses. Computational simulations are conducted to validate and analyze the performance of each proposal, varying various parameters of the algorithms and the network. All such Proposals are compared with other methods described in the literature, highlighting the superiority of the contributions presented in this work